Suicidal Ideation among In-School Adolescents in Enugu State, Nigeria: A Qualitative Approach - Ugwuoke, Anthony (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
The study was aimed at determining suicidal ideation among in-school adolescents in Enugu state, Nigeria. Case study design was employed to execute the study. The population for the study was 149,028 in-school adolescents in public secondary schools owned by Enugu State Government and the sample for the study was 24 participants. Focus group discussion was utilized to generate data. The qualitative data obtained were transcribed and utilized for discussions. Results from the study indicated that suicidal ideation was high among the in-school adolescents and was higher among the older group than at younger age. From the findings it was suggested that suicide education be initiated in secondary schools in Enugu state to prevent suicide idea from arising among the inschool adolescents. Additionally, as in-school adolescents grow older, school health educators in conjunction with guidance counselors should maintain surveillance on them to prevent suicidal ideation from progressing to attempted or completed suicide.